Epidemiological Characteristics of Sporadic Nosocomial COVID-19 Infections From June 2020 to June 2021 in China: An Overview of Vaccine Breakthrough Infection Events - He, Zhigang; Xiang, Hongbing; Manyande, Anne; Xu, Weiguo; Fan, Li; Xiang, Boqi (Frontiers in Medicine, 2021)
The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) pandemic has wreaked havoc to human beings around the world. Although China quickly brought the Coronavirus disease (COVID-19) pandemic under control, there have been several sporadic outbreaks in different regions of China since then. This article describes the chronological nosocomial COVID-19 infection events that related to several sporadic outbreaks of SARS-CoV-2 in different regions of China. We reported epidemiological characteristics and management measures of sporadic nosocomial COVID-19 infections from June 2020 to June 2021 in China, specially focused on domestic COVID-19 breakthrough infection in China — a vaccinated healthcare professional working in the isolation ward of a designated COVID-19 hospital.